Therapeutic angiogenesis by vascular endothelial growth factor supplementation for treatment of renal disease. Issue 5 (September 2016) - Logue, Omar C.; McGowan, Jeremy W.D.; George, Eric M.; Bidwell, Gene L.
Abstract : Purpose of review: Vascular endothelial growth factors (VEGFs) influence renal function through angiogenesis, with VEGF-A being the most potent inducer of vascular formation. In the normal glomerulus, tight homeostatic balance is maintained between the levels of VEGF-A isoforms produced by podocyte cells, and the VEGF receptors (VEGFRs) expressed by glomerular endothelial, mesangial, and podocyte cells. Renal disease occurs when this homeostatic balance is lost, manifesting in the abnormal autocrine and paracrine VEGF-A/VEGFR signaling, ultrastructural glomerular and tubular damage, and impaired filtration. Recent findings: Preclinical disease models of ischemic renal injury, including acute ischemia/reperfusion, thrombotic microangiopathy, and chronic renovascular disease, treated with exogenous VEGF supplementation demonstrated therapeutic efficacy. These results suggest a therapeutic VEGF-A paracrine effect on endothelial cells in the context of acute or chronic obstructive ischemia. Conversely, renal dysfunction in diabetic nephropathy appears to occur through an upregulated VEGF autocrine effect on podocyte cells, which is exacerbated by hyperglycemia. Therefore, VEGF supplementation therapy may be contraindicated for treatment of diabetic nephropathy, but specific results will depend on dose and on the specific site of VEGF delivery. A drug delivery system that demonstrates cell specificity for glomerular or peritubular capillaries could be employed to restore balance to VEGF-A/VEGFR2 signaling, and by doing so, prevent the progression to end-stage renal disease. Summary: The review discusses the preclinical data available for VEGF supplementation therapy in models of renal disease.